Pengaruh Penambahan Abu Sekam Padi Terhadap Kuat Tekan Beton - Hamkah Hamkah; Alila Alila; Abraham Tuanakotta; Betheny Amahoru (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
Agricultural waste is waste derived from agricultural production, such ash, produced from combustion, has high pozzolanic properties due to its silica content and can be founf in areas with extensive rice fields village, kairatu district, wets seram regency, maluku. the method used is an experimental method in the laboratory using a partial cement substutute in the form of rice husk ash with varying dosages of 0%, 5%, 10% and 15% of the amount of cement tested at the ages of 7 and 28 days. the results of the study found that there was a decrease in pressure strength. the more percentage of rice husk ash used, the more the compressive strength of concrete decreases compared to normal concrete 0% (19.1 mpa), concrete with asp 5% (15.3 mpa) decreases by 19.9%, concrete with asp 10% (13.0 mpa) decreases by 31.9%, and the decrease for concrete with asp 15% (12.1 mpa) is 36.6% of normal concrete and rice husk ash to the slump, which is an increase in slump value. the slump value on normal concrete is 7.5 cm, concrete with an asp of 5% (9.5 cm) experiences a percentage increase in slump value of 26.7%, concrete with an asp of 10% (10cm) of 33.3% and concrete with an asp of 15% (11 cm) experiences a percentage increase of 46.7% from normal concrete.